Development and Validation of the Clinical Nurses' Job Crafting Scale. - Eunha Jeong; Sujeong Han (Journal of Korean Academy of Nursing Administration, 2025)
Purpose: The study was to develop a Clinical Nurses' Job Crafting Scale (CN-JCS) and examines its validity and reliability. Methods: Data were collected from 423 clinical nurses working in general hospitals. The CN-JCS was developed according to DeVellis's step sclae development guidelines. The CN-JCS was assessed for content validity, construct validity, item convergence/discrimination, convergent validity, and internal consistency. Results: In the exploratory factor analysis, five factors and 20 items were selected. Construct validity was examined using confirmatory factor analysis, and the model fit was good. The Conceptual reliability was greater than .70 and average variance extracted value was greater than .50, indicating discriminant validity. Convergent validity was confirmed through correlations between the CN-JCS, psychological empowerment and work engagement. The scale's reliability was established with a Cronbach's alpha of .90. The CN-JCS employs a 5-point Likert scale across 20 questions, gauging aspects such as giving meaning to work, changing the structure of work, exploring and communicating, pursuing relationship change, and positive attitude toward change. Conclusion: The CN-JCS can be used to accurately assess the job craft of clinical nurses, and the measured level can be used as baseline data to improve awareness and education of nurses' job craft.